Cross-population proteome-wide mendelian randomization study identifies likely causal proteins for cardiovascular diseases - Hua Zhong; Jingjing Zhu; Shuai Liu; Hoi Tung Hilton Wong; Yiqiang Zhang; Hung N. Luu; Qing Wu; Xuexia Wang; Lang Wu (Molecular Genetics and Genomics, 2026)
Blood proteins may play causal roles in cardiovascular diseases (CVDs) such as heart failure (HF) and peripheral artery disease (PAD). Proteome-wide Mendelian randomization (MR) has been widely used to prioritize drug targets for CVD in European populations, but its application to non-European populations remains limited. We conducted a proteome-wide MR analysis to evaluate the potential causal effects of 2,922 plasma proteins on five CVDs—atrial fibrillation (AF), coronary artery disease (CAD), HF, ischemic heart disease (IHD), and PAD. Analyses were performed across African (n = 931), East Asian (n = 262), and European (n = 10,840) populations using genetic instrument data from the UK Biobank cohort. Significant associations were further examined with genetic colocalization to strengthen causal inference. Using MR and colocalization analyses, we identified 53 significant protein–CVD associations across multi-populations, including 16 in African, six in East Asian, and 31 in European populations, respectively. Cross-population comparisons revealed four protein–CVD associations unique to African population and another four specific to East Asian population. Integration with clinical trial data prioritized 14 protein–disease pairs as promising candidates for therapeutic development or drug repurposing. Our findings highlight the value of proteome-wide MR in evaluating drug target applicability across populations. Several protein–disease associations were population-specific, emphasizing the need for inclusive genetic research to inform precision medicine in CVD prevention and treatment.